The global financial crisis: Implications for capital to agribusiness - Ahrendsen, Bruce L. (Applied Studies in Agribusiness and Commerce, 2012)
The global economy has continued to experience lingering effects of the global financial crisis that began in 2007. Although attention was initially given to the liquidity crisis and survival of some the world’s largest corporations and institutions, the financial crisis is likely to have long-lasting implications for agribusiness. As the world slowly recovers from the crisis, another round of problems are emerging as governments and international institutions attempt to unwind the positions they took in an effort to prevent the global economic bubble from bursting. Perhaps the most problematic factor for businesses is access to capital in sufficient amounts and at affordable rates. Governments and institutions, particularly in the United States (U.S.) and the European Union, have increased their financial obligations as the result of activities taken to curtail the economic crisis. These financial obligations and the associated financial risks place pressure on financial markets and tend to restrain the availability of capital and increase the cost of capital for businesses. However, the U.S. agricultural credit market has not experienced problems to the same extent as general business (commercial and industrial) and real estate credit markets have. In general, U.S. farm businesses have a strong balance sheet, adequate repayment capacity, sufficient amount of assets to offer collateral for loans, and reasonable profits. Thus, U.S. farm businesses have had an ample supply of credit at relatively low interest rates.